In vitro and in vivo activities of sparfloxacin against Mycoplasma pneumoniae. - Kaku, M (1994)
The in vitro and in vivo activities of sparfloxacin against Mycoplasma pneumoniae were compared with those of erythromycin, levofloxacin, ofloxacin, and minocycline. The MICs of sparfloxacin, erythromycin, levofloxacin, ofloxacin, and minocycline for 90% of the 43 M. pneumoniae strains tested were 0.063, 0.016, 0.5, 1, and 0.5 microgram/ml, respectively. In the experimental pulmonary M. pneumoniae infection model in Syrian golden hamsters, sparfloxacin was as effective as erythromycin when orally administered at 15 mg/kg twice daily for 5 days and more effective than erythromycin when orally administered at 10 mg/kg once daily for 5 days. Sparfloxacin was more effective than levofloxacin and ofloxacin in both dosing regimens. The peak concentrations of sparfloxacin in hamster sera after administration of single oral doses of 15 mg/kg were almost the same as those in human sera after administration of single oral doses of 200 mg (the usual clinical dose), and the half-life of sparfloxacin in hamster serum was shorter than that in human serum after administration of a single oral dose of 200 mg. These results suggest that sparfloxacin may be clinically useful for the treatment of M. pneumoniae infections.